2019
DOI: 10.1002/chem.201805370
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Bismuth Heterovalent Doping on the Structural and Photophysical Properties of CH3NH3PbBr3 Halide Perovskite Crystals with Near‐IR Photoluminescence

Abstract: Ac omprehensive study unveiling the impacto f heterovalent doping with Bi 3 + on the structural,s emiconductive, and photoluminescent properties of as ingle crystal of lead halide perovskites (CH 3 NH 3 PbBr 3 )i sp resented.A si ndicatedb ys ingle-crystal XRD, ap erfect cubic structure in Bi 3 + -doped CH 3 NH 3 PbBr 3 crystals is maintainedina ssociation with as light lattice contraction. Time-resolved andp owerdependent photoluminescence( PL) spectroscopy illustrates ap rogressivelyq uenched PL of visible e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 52 publications
10
38
0
2
Order By: Relevance
“…The Urbach energy 41,42 is lower in pristine MAPbBr2.5Cl0.5 and MAPbBr3 MHPSCs than in the Bidoped and Ag-doped layers, which indicates that more traps exist inside the doped layers. The band gap remains at 2.19 eV for the doped MAPbBr3 MHPSC as reported previously 33,43 . Further, the play the role of dopants, as calculated in a previous report 33 .…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The Urbach energy 41,42 is lower in pristine MAPbBr2.5Cl0.5 and MAPbBr3 MHPSCs than in the Bidoped and Ag-doped layers, which indicates that more traps exist inside the doped layers. The band gap remains at 2.19 eV for the doped MAPbBr3 MHPSC as reported previously 33,43 . Further, the play the role of dopants, as calculated in a previous report 33 .…”
Section: Resultssupporting
confidence: 84%
“…The band gap remains at 2.19 eV for the doped MAPbBr3 MHPSC as reported previously 33,43 . Further, the play the role of dopants, as calculated in a previous report 33 . The Ag-doped p-type layer may be formed due to the Ag dopants, leading to a higher excess of Br in the MAPbBr3 MHPSC and making the MHPSC more p-type 37 .…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…[116] In addition, at low concentration of doping, Bi 3þ dopants have been found to fill the trap states and improve ionic conductivity of the perovskite; at a higher concentration of doping, they act as nonradiative recombination centers, leading to a transition from bimolecular recombination in pristine MAPbX 3 perovskites to a dominant trap-assisted monomolecular recombination process. [117,118] Abdi-Jalebi et al reported doping of MAPbI 3 with monovalent cations (Na þ , Cu þ , and Ag þ ) having an ionic radius similar to that of bivalent lead cations. Such heterovalent substitution has led to an improvement in the PCE of solar cells based on doped materials.…”
Section: Inorganic Dopantsmentioning
confidence: 99%
“…[ 116 ] In addition, at low concentration of doping, Bi 3+ dopants have been found to fill the trap states and improve ionic conductivity of the perovskite; at a higher concentration of doping, they act as nonradiative recombination centers, leading to a transition from bimolecular recombination in pristine MAPbX 3 perovskites to a dominant trap‐assisted monomolecular recombination process. [ 117,118 ]…”
Section: Defect Passivation In Abx3mentioning
confidence: 99%